Stress, cognitive appraisal, and burnout in social workers of residential child care - Diana Rocha; António Rui Gomes; Ana Cristina Costa Figueiredo (Revista de Psicología, 2022)
Stress and burnout are global epidemics that may cause negative consequences for workers and organizations. Social workers of residential child care are especially at risk, due to the inherent characteristics of their work. Subsequently, this study aimed to analyse these professional’s stress, cognitive appraisal, and burnout. The sample included 92 social workers (90.2% female and 9.8% male) with ages between 25 and 64 years old (M = 38.08; SD = 7.91). The evaluation protocol included a sociodemographic questionnaire, the Stress Questionnaire for Health Professionals, the Primary and Secondary Cognitive Appraisal Scale, and the Shirom-Melamed Burnout Measure. Results indicated that 58% of professionals assumed high levels of general stress, and that physical fatigue and cognitive weariness were the burnout dimensions with higher values. The combination of sociodemographic variables, stress factors and cognitive appraisal were important to explain the burnout experience and can contribute to design interventions directed to these professionals.